21. ASSESSING EARLY INITIATION OF BREASTFEEDING PRACTICE AMONG POSTPARTUM WOMEN IN BOKEO PROVINCIAL HOSPITAL, LAO PEOPLE’S DEMOCRATIC REPUBLIC (LAO PDR) DURING 2022-202 (Vietnam Journal of Community Medicine, 2025)
Introduction: This paper aimed to assess the change of the early initiation of breastfeeding (within one hour of birth) amongst postpartum women in a hospital-based intervention during 2022-2023.Methods: The study used a quasi-experimental design that used data before and after an intervention to evaluate the effectiveness of the intervention. The total number of postpartum women was 400 with 2 data collection periods: Jan-Apr, 2022 and Sep-Dec, 2023.Results: The results showed that early initiation of breastfeeding amongst postpartum women increased from 47.5% to 97.7%, with an 50.2% increase in percentage (p
Keywords: early initiation of breastfeeding; maternal and child health care; hospital-based intervention; Lao PDR